2004
DOI: 10.1148/radiol.2302011842
|View full text |Cite
|
Sign up to set email alerts
|

Intervertebral Disk Calcification of the Spine in an Elderly Population: Radiographic Prevalence, Location, and Distribution and Correlation with Spinal Degeneration

Abstract: IDC is common in elderly persons, especially in the annulus fibrosus and lower thoracic spine. The prevalence of IDC increases with age and extent of disk space loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
95
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 10 publications
2
95
0
1
Order By: Relevance
“…According to the literature the prevalence of intervertebral disk calcification increases with age and extent of disk space loss. This was [4]. Another histological study from Gries et al [7] showed no correlation between early histological changes in lumbar disks and the associated facet joints (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…According to the literature the prevalence of intervertebral disk calcification increases with age and extent of disk space loss. This was [4]. Another histological study from Gries et al [7] showed no correlation between early histological changes in lumbar disks and the associated facet joints (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Discal calcification is reported to be found incidentally on 5 % of chest and 6 % of abdominal radiographs and in 70 % of postmortem examinations of adults [2]. These are generally asymptomatic and associated with an underlying predisposing systemic condition such as hyperparathyroidism, chondrocalcinosis and haemochromatosis [3]. Idiopathic symptomatic CD in adults is extremely rare and currently, only eight cases have been reported [2,[4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Although 85 years have passed since Schmorl [1] first described herniations of the nucleus pulposus into the vertebral end-plates of the thoracic and lumbar spine, controversy still exists regarding the pathogenesis, etiology, epidemiology and clinical significance of these lesions [2][3][4][5][6]. It is still debated whether Schmorl's nodes (SNs) are symptomatically silent developmental or congenital aberrations of the normal vertebral anatomy or represent a common histopathological pathway for various and adverse metabolic, traumatic, infectious, degenerative or malignant factors.…”
Section: Introductionmentioning
confidence: 99%